Kajian Etanolisis In Situ Minyak Kelapa untuk Sintesis Etil Ester Asam Lemak - Ijirana dan Afadil Ijirana dan Afadil (Biocelebes, 2009)
There are several aim of this research, consist of: 1) to find out optimum concentration catalyst H2SO4 in synthesis of ethyl ester coconut oil fat acid when FFA contained in coconut flour more than 5 %, 2) to find out concentration of catalyst NaOH (percent v/v) that produce the higher fat acid ethyl ester product, 3) to find out ratio of ethanol 95 % / coconut flour, and 4) to find out the best reaction temperature of coconut oil ethanolysis in situ that produce ethyl ester coconut oil fat acid in higher yield. The first step is to know water contain on coconut flour. The second is to know oil contain in coconut flour using sochletation method. FFA analyzed was done to find out how many reaction will be done, transestherification and esterification. Esterification was not done because FFA contained only 2 % (not more than 5%). From this research, we can conclude that selected reaction condition are: ratio coconut flour with ethanol 95%, 1:5, concentration of catalyst, NaOH 1,2% and reaction temperature 55oC. Key words: Ethanolysis in situ, coconut oil, fat acid ethyl ester syntesis.